A Proposed Design of Unit Cell of Metamaterial for 5G Mobile Communication - Jamal Mohammed Rasool (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexIn this manuscript a design of metamaterial unit cells which are new artificial materials made of periodic arrangement much smaller than the guided wavelength, are proposed which are suitable to work for 5G mobile communication working with millimeter frequency band at 28 GHz due the high demand for the frequency spectrum for mobile networks .The structures of unit cells were simulated using High Frequency Structure Simulator HFSS software. The design starts with the metamaterial structure which is composed of double rectangular (DRR) and circular split ring resonator (DSRR). The results of simulation showed very good results such as wide operating frequency band which is 1.34 GHz with very law radiation losses the unit cell designed to overrun the radiation losses which are appear with the work of metamaterials.